Trapping single cells: Comparison between Sandwiched Insulation with Back Contact (SIBC) and Planar Biochip - Ibrahim, Siti Noorjannah; Murray, Lynn; Evans, John J.; M.Alkaisi, Maan (Trans Tech Publications, 2012)
AC electrokinetics is one of many methods used to move particles in microfluidic channels. This paper presents single cell trapping efficacy using dielectrophoresis (DEP) force of two biochip designs; a planar biochip and the new sandwiched-insulation with back contact (SIBC) biochip. The new biochip, is structured on a glass slide, consists of microelectrode arrays patterned on top of Nickel-Chromium (NiCr) and Gold (Au) layers. Prior to the microelectrode patterning, a back contact layer of NiCr and Au was coated with SU-8 2005. Then, the SU-8 2005 or the insulation layer was patterned with arrays of microcavities. In contrast, the planar biochip consists of 2 layers; an SU-8 2005 insulation layer and NiCr and Au metal layers constructed on a Silicon Nitride (Si3N4) substrate. The electric field intensity results simulated using Comsol v3.5a software indicated that DEP force generated from the SIBC biochip are greater than the planar biochip design. Results from experiment with polystyrene microbeads and Ishikawa cancer cells also showed that the SIBC biochip has higher trapping efficiency than the planar biochip. These promising results indicate that the SIBC biochip is capable of trapping single cells and can be used to facilitate studies on intracellular activities using surface the replicating technique known as the Bioimprint technique.